Patient perceived service quality profiles of primary health care associated with usual source of care: a latent profile analysis - Zhang, Li; Wang, Baokai; Xu, Qi (Frontiers in Medicine, 2025)
BackgroundUnder the context that the Chinese government has taken many incentives to promote the development of primary health care (PHC), the extent to which patients choose PHC as their usual source of care (USC) and how patient perceived service quality affects this choice remains unclear. This study aimed to explore potential profiles of patient perceived service quality of PHC, analyse sociodemographic and health-related characteristics among perceived service quality subgroups, and investigate the association between patient perceived service quality and usual source of PHC.MethodsA cross-sectional survey was conducted in Shandong Province, China, from July 2023 to August 2023. 3025 patients were selected using a multistage stratified sampling method. Latent profile analysis was used to explore the profiles of patient perceived service quality of PHC. Multiple logistic regression analysis was adopted to identify the predictors of different profiles, and the binary logistic regression was used to examine the association between perceived service quality profiles and usual source of PHC.ResultsThe model fitting indices of patient perceived service quality supported three profiles which were as follows: low perceived service quality group at 20.23%, moderate perceived service quality group at 56.50%, and high perceived service quality group at 23.27%. Age, educational level, personal monthly income, and self-rated health were predictors of different profiles. Furthermore, patients reporting high perceived service quality of PHC were more likely to regard PHC as the USC compared with those with low perceived service quality (OR = 2.748, 95% confidence interval = 2.112–3.575).ConclusionStrengthening patient perceived service quality can encourage them to regard PHC facilities as the USC. PHC facilities should provide customized and tailored health services that focus on individuals’ specific needs and preferences to improve patient perceived service quality.